2017
DOI: 10.1002/joc.5053
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of changes in atmospheric dynamics and dust activity over southwest Asia using the Caspian Sea–Hindu Kush Index

Abstract: This study examines the influence of the Caspian Sea–Hindu Kush Index (CasHKI) on local and synoptic meteorology as well as on dust emissions over southwest (SW) Asia by means of National Center for Environmental Prediction/National Center for Atmospheric Research (NCEP‐NCAR) re‐analysed mean sea‐level pressure (MSLP), geopotential height at 700 hPa and surface meridional wind, along with meteorological data at Zabol, east Iran and Meteosat/Infrared Difference Dust Index (IDDI) retrievals. The analysis focuses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 83 publications
1
20
0
Order By: Relevance
“…The seasonal upper atmospheric systems indicated that while in winter, the Arabian Peninsula is affected by the trough of the northern cyclone, it is affected by the ridge of the subtropical anticyclone during the other seasons. In addition, the wind patterns associated with atmospheric systems influence the area change from the anticyclonic wind in winter, represented by the wind systems associated with dust, as described in previous studies (Barkan and Alpert, ; Shalaby et al ., ), to the north‐northeastern wind in summer and spring, represented by what is called the Shamal system (Hamidi et al ., ; Houssos et al ., ; Kaskaoutis et al ., ), and then shifting to an anticyclonic wind in autumn.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The seasonal upper atmospheric systems indicated that while in winter, the Arabian Peninsula is affected by the trough of the northern cyclone, it is affected by the ridge of the subtropical anticyclone during the other seasons. In addition, the wind patterns associated with atmospheric systems influence the area change from the anticyclonic wind in winter, represented by the wind systems associated with dust, as described in previous studies (Barkan and Alpert, ; Shalaby et al ., ), to the north‐northeastern wind in summer and spring, represented by what is called the Shamal system (Hamidi et al ., ; Houssos et al ., ; Kaskaoutis et al ., ), and then shifting to an anticyclonic wind in autumn.…”
Section: Discussionmentioning
confidence: 97%
“…At the same time, the western anticyclone has a strong effect on the region (summer season) or exhibits a pronounced ridge (autumn season). In addition, the atmospheric systems in the summer pattern interact and form a northerly wind over the eastern Arabian Peninsula (Hamidi et al ., ; Houssos et al ., ; Kaskaoutis et al ., ) and an anticyclonic wind pattern over the southeastern Arabian Peninsula, which is in agreement with the results reported by Rezazadeh et al . (), Barkan and Alpert (), and Shalaby et al .…”
Section: Discussionmentioning
confidence: 97%
“…In their classification of dust systems, Hamidi et al (2013) found that the local extent of the SH is related to the development of the frontal dust system regime over the region. Moreover, Kaskaoutis et al (2016Kaskaoutis et al ( , 2017 developed a meteorological index based on the differences in sea level pressure (SLP) anomalies between high-pressure systems over the Caspian Sea region and low-pressure systems over the Hindu Kush area, as the intensities of these systems are related to the production of strong northerly winds and an increase in dust activity over southwest Asia.…”
Section: Introductionmentioning
confidence: 99%
“…Aerosols are emitted into the Earth's atmosphere from various natural and anthropogenic sources. Aerosols from these heterogeneous sources are transported by wind and are distributed across the globe, depending on the prevailing meteorological conditions (Tanner and Law, ; Cheng et al ., ; Zhao et al ., ; Kaskaoutis et al ., ). The spatial distribution of atmospheric aerosols is important information required to assess their impact on the environment, which in turn necessitates a timely estimate of aerosol sources.…”
Section: Introductionmentioning
confidence: 97%